1981
DOI: 10.3189/s002214300001128x
|View full text |Cite
|
Sign up to set email alerts
|

Creep and Fabrics of Polycrystalline Ice Under Shear and Compression

Abstract: ABSTRACT. Creep tests were performed in torsion and torsion-compression on polycrystalline ice at temperatures near the melting point. Syntectonic recrystallization occurs at strains of the order of 2-3%, leading to a rapid increase in strain-rate. It is shown that the increase of creep-rate during tertiary creep arises from the development of fabrics favouring the glide on basal planes but also from the softening processes associated with recrystallization. The c-axis fabric of recrystallized ice developed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 16 publications
4
34
1
Order By: Relevance
“…Actually, during the compressive creep tests, the slip direction rotates away from the compression axis if one considers each crystal individually. Compared with some previous data, which show a strong girdle-shaped orientation at strains above 15% (Duval, 1981;Azuma and Higashi, 1985), the $10% strain is rather small to generate such a girdle-shaped fabric in our tests. The reason for this phenomenon is not clear at this stage.…”
Section: Microstructural Evolutioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Actually, during the compressive creep tests, the slip direction rotates away from the compression axis if one considers each crystal individually. Compared with some previous data, which show a strong girdle-shaped orientation at strains above 15% (Duval, 1981;Azuma and Higashi, 1985), the $10% strain is rather small to generate such a girdle-shaped fabric in our tests. The reason for this phenomenon is not clear at this stage.…”
Section: Microstructural Evolutioncontrasting
confidence: 40%
“…There are a number of studies (Duval, 1981;Jacka, 1984a;Jacka and Maccagnan, 1984;Azuma and Higashi, 1985;Wilson and Sim, 2002) concerning fabric development in laboratory-prepared and glacier ice. These studies examined fabric development under compression and shear.…”
Section: Introductionmentioning
confidence: 99%
“…12) have been observed in previous experiments (Kamb, 1972;Duval, 1981) but are poorly understood. However, there seems to be consensus that such fabrics are indicative of recrystallization of ice at or near its pressure-melting temperature under simple shear and compression normal to the plane of shear (Hooke, 2005;Cuffey and Paterson, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…Results of laboratory experiments have indicated that strain-softening, particularly with added impurities such as HF (Jones, 1967;Jones and Glen, 1969) and HCl (Nakamura and Jones, 1970), can occur in H 2 O ice. In some cases, this softening has been attributed to the development of preferred orientations favoring basil slip (Steinemann, 1954;Kamb, 1972;Duval, 1979Duval, , 1981. Strain-softening has also been found to occur during laboratory strength experiments of cryogenic ice, and was attributed to dislocation multiplication and velocity-limited dislocation glide (Weertman, 1983;Durham et al, 1983Durham et al, , 1992.…”
Section: Possible Detachment Formation Mechanisms On Icy Satellitesmentioning
confidence: 92%